Assessment of animal feed resource availability in Southern Karnataka region - RAJU, S S; ANANDAN, S; ANGADI, U B; ANANTHRAM, K; PRASAD, C S; RAMACHANDRA, K S (The Indian Journal of Animal Sciences, 2014)
Animal feed resource availability was assessed based on secondary data in Southern Karnataka region compristng 7 districts. Distribution and composition of livesLock revealed that the region accounted for 49 and 48% of total state sheep and poultry population, respectively. High percentage of crossbred cattle (26.10%) among adult females wilh high crossbred population in the districts of Bangalore urban (64.69%), Kolar (45.71%) and I3angalore rural (30.30%) indicated that the animal husbandry activities are practiced more on commercial lines in the region. The region had a total DM availability of 10.31 m tonnes from different feed resources. Crop residues contributed for more than 70% of total DM available in the region. Major portion (58%) of the green DM forage availability is contributed from the gross cropped area in all the districts of the region. The contribution from the forest area was minimal within the region as a whole. The DM availabilityl RLU/day for the region is 8.05 kg with the values ranging from 3.92 kg in Bangalore urban district to 12.33 kg in Chitradurga district. The study indicated that the existing situation ranges from low feed resource availability-high productivity to high feed resource availability-low productivity. Developing suitable strategies for etlicient utilization of existing feed resources would help in further increasing the animal productivitr in the region.